PERAN GANDA WANITA DALAM EKONOMI KELUARGA (Studi Kasus Pada Pedagang Wanita Pasar Klewer) - Bachtiar Suryo Bawono; Bambang Santosa (Universitas Sebelas Maret (UNS), 2020)
Women in the era of globalization have experienced significant changes. As women who previously were not played an active role in the labor market, many woman now play an active role in the world of work, especially in the trade sector. Based on data from the Surakarta City Gender Study and Social Workers Association (PRP) Study, 72% of the traditional market trader population is women. In addition to having a positive impact, increasing women's participation in the world of work also has a negative impact on women themselves. As women as workers will experience double burden problems. It means women who work will have two responsibilities, that is public work responsibilities and domestic work responsibilities.Therefore, the author would like to know how the Dual Role of Women in the Family Economy in Women's Traders' Families in Surakarta City's Klewer Market? This study uses gender analysis techniques Hardvard-1 or HAF method combined with interactive analysis methods. The results showed that the first category of informants only wives who traded in the market showed that, the wife played a role in increasing family income. The initial income of a husband working alone is only able to meet primary needs. After the wife trades, the husband and wife can meet secondary needs and increase family purchasing power. In the access and control of family economic resources, they tend to be dominated by husbands. The informants of both husband and wife trading together in a kios then the role of the wife does not affect the ups and downs of trading income. In accessing and controlling economic resources the family runs in balance.